Effects of 12 weeks of power-oriented resistance training plus high-intensity interval training on metabolic syndrome factors in older people with COPD - Romero-Valia Lucia; Baltasar-Fernandez Ivan; Rodriguez-Lopez Carlos; Losa-Reyna Jose; Alfaro-Acha Ana; Guadalupe-Grau Amelia; Ara Ignacio; Alegre Luis M.; García-García Francisco J.; Alcazar Julian (Translational Exercise Biomedicine)
To assess the effects of an exercise training program combining power-oriented resistance training (RT) and high-intensity interval training (HIIT) on metabolic syndrome (MetS) markers in older people with COPD.